Intermediate pressure-normalized principal wall strain values are associated with increased abdominal aortic aneurysmal growth rates - Zottola, Zachary R.; Kong, Daniel S.; Medhekar, Ankit N.; Frye, Lauren E.; Hao, Scarlett B.; Gonring, Dakota W.; Hirad, Adnan A.; Stoner, Michael C.; Richards, Michael S.; Mix, Doran S. (Frontiers in Cardiovascular Medicine, 2023)
Introduction Current abdominal aortic aneurysm (AAA) assessment relies on analysis of AAA diameter and growth rate. However, evidence demonstrates that AAA pathology varies among patients and morphometric analysis alone is insufficient to precisely predict individual rupture risk. Biomechanical parameters, such as pressure-normalized AAA principal wall strain (ερ+¯/PP, %/mmHg), can provide useful information for AAA assessment. Therefore, this study utilized a previously validated ultrasound elastography (USE) technique to correlate ερ+¯/PP with the current AAA assessment methods of maximal diameter and growth rate. Methods Our USE algorithm utilizes a finite element mesh, overlaid a 2D cross-sectional view of the user-defined AAA wall, at the location of maximum diameter, to track two-dimensional, frame-to-frame displacements over a full cardiac cycle, using a custom image registration algorithm to produce ερ+¯/PP. This metric was compared between patients with healthy aortas and AAAs (≥3 cm) and compared between small and large AAAs (≥5 cm). AAAs were then separated into terciles based on ερ+¯/PP values to further assess differences in our metric across maximal diameter and prospective growth rate. Non-parametric tests of hypotheses were used to assess statistical significance as appropriate. Results USE analysis was conducted on 129 patients, 16 healthy aortas and 113 AAAs, of which 86 were classified as small AAAs and 27 as large. Non-aneurysmal aortas showed higher ερ+¯/PP compared to AAAs (0.044 ± 0.015 vs. 0.034 ± 0.017%/mmHg, p = 0.01) indicating AAA walls to be stiffer. Small and large AAAs showed no difference in ερ+¯/PP. When divided into terciles based on ερ+¯/PP cutoffs of 0.0251 and 0.038%/mmHg, there was no difference in AAA diameter. There was a statistically significant difference in prospective growth rate between the intermediate tercile and the outer two terciles (1.46 ± 2.48 vs. 3.59 ± 3.83 vs. 1.78 ± 1.64 mm/yr, p = 0.014). Discussion There was no correlation between AAA diameter and ερ+¯/PP, indicating biomechanical markers of AAA pathology are likely independent of diameter. AAAs in the intermediate tercile of ερ+¯/PP values were found to have nearly double the growth rates than the highest or lowest tercile, indicating an intermediate range of ερ+¯/PP values for which patients are at risk for increased AAA expansion, likely necessitating more frequent imaging follow-up.